Comparison of the efficacy of interlesional corticosteroid and silicone gel for keloid treatment: a review article - Limanda, Claudia Felicia; Widhiartini, Ida Ayu Alit (International Journal of Research in Medical Sciences, 2023)
Keloid is an abnormal scar associated with various skin problems including physical and psychological distress. Keloid is often presented as skin itching, swelling, and pain with possible complications such as recurrent sequelae and stigma. Prevention and treatment of this problem include topical non-invasive and invasive options, such as silicon-based products and corticosteroids which are available in the market. Silicon is stated as a standard product, however, is used more often as a combination with corticosteroids than single use. Effectiveness of both products have been discussed separately in previous studies, making it unclear which one is more superior. Thus, a review is needed to ensure their uses in daily practice and to determine their superiority as a single or combination treatment in order to apply them efficiently. Aim of this study is to compare effectiveness of corticosteroids and silicone products to prevent or treat keloid. Keywords such as "keloid," "corticosteroid," and "silicone products" were used in PubMed, national library of medicine, ResearchGate, and dermatology textbooks. Journals found were analyzed for their validity and reliability before the compilation of this review article. Results found stated that both silicone pharmaceutical products and corticosteroids have their own benefits and risks. In addition, according to their treatment phase, they can be used as single or combination treatment. However, due to limited existing studies found, further research is necessary.